ROLE OF THE MECHANISM OF RESOURCE SECURITY SYSTEMS OF ECONOMIC SECURITY OF THE SECURITY IN THE SECURED IMPLEMENTATION OF THE LEGAL STRATEGY OF THE SECURITY - ASAMOAH CHEREMEH, J.; MATIUKH, S. (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The statistic has shown the particularity of the resource security of the system and the economic security of the enterprise in the context of the implementation of the strategic goals of the enterprise. The interpretation of the terms "mechanism" and "mechanism of control" has been introduced. The interpretation of the term "mechanism" is a dual of nature, the fragments can be looked at from the position of the mechanistic approach to all spheres, de-mechanization becomes stagnant. It was assigned to the mechanism of the mechanism of resource security of the system and economic security of the enterprise at the secure implementation of the foreign strategy of the enterprise. It is concretized that the basis of the function of such a mechanism is the backbone strategy of the enterprise with strategic goals, the specific establishment of the system and the economic security, that will consume the system itself. Resource safety is due to the folding and distribution of the system and economic safety, as well as the intensity of threats to the business. At the same time, two main aspects are required. The first one is costs in the function and in the form of resource security of the function of the system and economic security of the enterprise not guilty of overhauling the boundary-permissible norms (taking into account the principle of costs–profit). The other - a large amount of visual resources is guilty of being sufficient for the implementation on the proper level of the functional functions by the system of economic security of the enterprise. Adequacy of the vision of resources for the functioning of the system and the economic security of the enterprise, depending on the ambiguity of the reaction of managers in the old age. The price is summed up by the foldability of the non-average effect for the operational processes of the function of such a system. It is indicated that when planning the resource safety of the system and the economic safety of the enterprise, it is necessary to provide the capacity to transfer the reserve for maximum demand. A readily predicted list of resources necessary for securing the functions of the system and the economic security of the enterprise is satisfied with the folding task of the functions of such a system in different modes.